Celadon glaze, ceramics and preparation method thereof
By using matrix materials such as cooked talc and adding modifiers and modified dolomite as functional additives, celadon glaze water was prepared, and the problems of insufficient wear resistance, impact strength and delicate texture of the existing celadon glaze water were solved, and the high performance and acid and alkali resistance of ceramics were achieved.
Patent Information
- Application Number
- CN202510037949.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing celadon glaze water has insufficient wear resistance, impact strength and texture, and has poor acid and alkali resistance, which limits the efficiency of the product.
Celite glaze water is prepared by wet ball milling and sintering treatment.
It significantly improves the wear resistance, impact strength and delicate texture of ceramics, and enhances its acid and alkali resistance stability, and improves the efficiency of product use.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a celadon glaze, ceramics and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain, and is also a kind of arts and crafts in my country. As early as the Neolithic Age, my country already had rough and simple painted pottery and black pottery. Pottery and porcelain have different textures and properties. Pottery is made of clay with high viscosity and strong plasticity as the main raw material. It is opaque, has fine pores and weak water absorption, and makes a turbid sound when struck. The celadon glaze used in existing ceramic products has poor surface wear resistance and impact resistance. At the same time, the product has poor texture and delicateness, and the product has poor acid and alkali resistance stability, which limits the product's efficiency. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a celadon glaze, ceramics and a preparation method thereof to solve the problems raised in the above-mentioned background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a celadon glaze comprising the following raw materials in parts by weight:
[0006] 10-15 parts of cooked talc, 5-8 parts of added modifier, 4-7 parts of ball clay, 4-7 parts of modified dolomite, 2-4 parts of Longquan porcelain clay, 2-4 parts of zinc oxide, and 2-4 parts of tin oxide.
[0007] Preferably, the preparation method of adding a modifier is:
[0008] S01: Add 2-5 parts of zirconium silicate and 1-3 parts of silane coupling agent KH550 to 5-8 parts of cerium nitrate solution by weight, then add 2-3 parts of silicon carbide powder, stir well, and obtain zirconium silicate liquid;
[0009] S02: immersing the boron nitride in a 5% chitosan solution having a mass fraction of 3-5 times the total weight of the boron nitride, stirring evenly to obtain a boron nitride solution;
[0010] Adding boron nitride liquid to zirconium silicate liquid in a weight ratio of 2:5 and stirring, and completing the stirring to obtain a zirconium silicate agent doped with boron nitride;
[0011] S03: Add additives in an amount of 10-15% of the total weight of the boron nitride-doped zirconium silicate agent to the boron nitride-doped zirconium silicate agent, and ball-mill at a speed of 750-850 r / min for 2 hours. After the ball-milling is completed, filter and dry to obtain an additive modifier.
[0012] Preferably, the mass fraction of the cerium nitrate solution is 2-5%; the stirring speed of the stirring treatment is 550-750 r / min, and the stirring time is 1 hour.
[0013] Preferably, the preparation method of the additive is:
[0014] According to weight, 2-4 parts of yttrium oxide and 1-3 parts of silica powder are added to 4-7 parts of sodium silicate solution, and then 2-4 parts of nano-attapulgite and 1-2 parts of nano-silica sol are added, and the mixture is stirred and mixed thoroughly, and then filtered and dried to obtain an additive.
[0015] Preferably, the mass fraction of the sodium silicate solution is 2-5%.
[0016] Preferably, the modification method of the modified dolomite is:
[0017] S101: placing the dolomite in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400W. After the irradiation is completed, preheating at 60-65° C. for 1 hour to obtain pretreated dolomite;
[0018] S102: Mix 1-2 parts of urea solution and 2-4 parts of dopamine hydrochloride solution by weight, then add 2-3 parts of hydroxyapatite and 1-2 parts of sodium carboxymethyl cellulose, stir well, and obtain a modified solution;
[0019] The pretreated dolomite and the modified liquid were subjected to ultrasonic modification treatment in a weight ratio of 2:5. After the modification was completed, the modified dolomite was filtered and dried to obtain the modified dolomite.
[0020] Preferably, the mass fraction of the urea solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 4-6%; the ultrasonic power of the ultrasonic modification treatment is 400-450W, and the ultrasonic time is 1h.
[0021] The present invention also provides a method for preparing ceramics, using the celadon glaze, comprising the following steps:
[0022] Step 1: Prepare celadon glaze:
[0023] Weigh the raw materials of celadon glaze water by weight, and then wet-mill them thoroughly to obtain celadon glaze water;
[0024] Step 2: 10-15 parts of potassium feldspar, 4-7 parts of quartz, 3-5 parts of kaolin and 3-5 parts of bentonite are mixed and wet-milled at a speed of 1000 r / min for 1 hour to obtain a ball mill; the ball mill is pressed into a mold at a pressure of 15 MPa for 30 minutes to obtain a green body;
[0025] Step three: Apply celadon glaze to the surface of the body, and then sinter it. After sintering, a ceramic with celadon glaze is obtained.
[0026] Preferably, the glazing amount of the glazing is 520-550g / m 2 ; The sintering temperature of the sintering treatment is 1350°C and the sintering time is 5h.
[0027] The invention also provides a ceramic prepared by the ceramic preparation method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The ceramic of the celadon glaze of the present invention is prepared by wet ball milling of potassium feldspar, quartz, kaolin and bentonite to obtain a ball mill material, which is then pressed and formed into a green body. Talc, ball clay, Longquan porcelain clay, zinc oxide and tin oxide are used as matrix materials. Modifiers and modified dolomite are added as functional additives. The two are coordinated and coordinated to obtain the ceramic surface of the celadon glaze with excellent wear resistance and impact strength. At the same time, the product has a significant effect on the fine texture and the stability of the acid and alkali resistance of the product is significant.
[0030] 2. Adding modifiers, boron nitride is used to mix and permeate chitosan solution, and the boron nitride liquid can be better blended and stirred with zirconium silicate liquid. Zirconium silicate liquid is blended and coordinated with zirconium silicate, silane coupling agent KH550, cerium nitrate solution and silicon carbide powder. Through the mutual matching and assistance between the raw materials, the coordination and coordination effect of zirconium silicate, silicon carbide and boron nitride is optimized, thereby improving the performance coordination of the product, and the performance stability effect is significant. The additives are yttrium oxide and silica powder, which are coordinated with sodium silicate solution, and then coordinated with nano-attapulgite and nano-silica sol. Nano-attapulgite is used as the lamellar structure and then coordinated with silica powder. Through the mutual matching and assistance between the raw materials, the improvement is enhanced, so that the additives are better coordinated with the zirconium silicate agent doped with boron nitride, thereby coordinating and optimizing the product performance, thereby coordinating the product performance, and improving the acid resistance and stability of the product;
[0031] 3. Modified dolomite is treated with proton irradiation to optimize its activity performance. The modified liquid is prepared by mixing urea solution and dopamine hydrochloride solution, and then blended with hydroxyapatite and sodium carboxymethyl cellulose. The dolomite is further improved by adjusting the composition and efficiency of the raw materials. The modified dolomite has a better coordination effect with the added modifier, and the performance of the product is further improved. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A celadon glaze water of this embodiment includes the following raw materials in parts by weight:
[0034] 10-15 parts of cooked talc, 5-8 parts of added modifier, 4-7 parts of ball clay, 4-7 parts of modified dolomite, 2-4 parts of Longquan porcelain clay, 2-4 parts of zinc oxide, and 2-4 parts of tin oxide.
[0035] In this embodiment, the preparation method of adding a modifier is:
[0036] S01: Add 2-5 parts of zirconium silicate and 1-3 parts of silane coupling agent KH550 to 5-8 parts of cerium nitrate solution by weight, then add 2-3 parts of silicon carbide powder, stir well, and obtain zirconium silicate liquid;
[0037] S02: immersing the boron nitride in a 5% chitosan solution having a mass fraction of 3-5 times the total weight of the boron nitride, stirring evenly to obtain a boron nitride solution;
[0038] Adding boron nitride liquid to zirconium silicate liquid in a weight ratio of 2:5 and stirring, and completing the stirring to obtain a zirconium silicate agent doped with boron nitride;
[0039] S03: Add additives in an amount of 10-15% of the total weight of the boron nitride-doped zirconium silicate agent to the boron nitride-doped zirconium silicate agent, and ball-mill at a speed of 750-850 r / min for 2 hours. After the ball-milling is completed, filter and dry to obtain an additive modifier.
[0040] In this embodiment, the mass fraction of the cerium nitrate solution is 2-5%; the stirring speed of the stirring treatment is 550-750 r / min, and the stirring time is 1 hour.
[0041] In this embodiment, the preparation method of the additive is:
[0042] According to weight, 2-4 parts of yttrium oxide and 1-3 parts of silica powder are added to 4-7 parts of sodium silicate solution, and then 2-4 parts of nano-attapulgite and 1-2 parts of nano-silica sol are added, and the mixture is stirred and mixed thoroughly, and then filtered and dried to obtain an additive.
[0043] In this embodiment, the mass fraction of the sodium silicate solution is 2-5%.
[0044] In this embodiment, the modification method of the modified dolomite is:
[0045] S101: placing the dolomite in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400W. After the irradiation is completed, preheating at 60-65° C. for 1 hour to obtain pretreated dolomite;
[0046] S102: Mix 1-2 parts of urea solution and 2-4 parts of dopamine hydrochloride solution by weight, then add 2-3 parts of hydroxyapatite and 1-2 parts of sodium carboxymethyl cellulose, stir well, and obtain a modified solution;
[0047] The pretreated dolomite and the modified liquid were subjected to ultrasonic modification treatment in a weight ratio of 2:5. After the modification was completed, the modified dolomite was filtered and dried to obtain the modified dolomite.
[0048] In this embodiment, the mass fraction of the urea solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 4-6%; the ultrasonic power of the ultrasonic modification treatment is 400-450W, and the ultrasonic time is 1h.
[0049] A method for preparing ceramics in this embodiment, using the celadon glaze, comprises the following steps:
[0050] Step 1: Prepare celadon glaze:
[0051] Weigh the raw materials of celadon glaze water by weight, and then wet-mill them thoroughly to obtain celadon glaze water;
[0052] Step 2: 10-15 parts of potassium feldspar, 4-7 parts of quartz, 3-5 parts of kaolin and 3-5 parts of bentonite are mixed and wet-milled at a speed of 1000 r / min for 1 hour to obtain a ball mill; the ball mill is pressed into a mold at a pressure of 15 MPa for 30 minutes to obtain a green body;
[0053] Step three: Apply celadon glaze to the surface of the body, and then sinter it. After sintering, a ceramic with celadon glaze is obtained.
[0054] In this embodiment, the glazing amount is 520-550g / m 2 ; The sintering temperature of the sintering treatment is 1350°C and the sintering time is 5h.
[0055] A ceramic of this embodiment is prepared by the ceramic preparation method.
[0056] Embodiment 1: A method for preparing a ceramic, comprising the following steps:
[0057] Step 1: Prepare celadon glaze:
[0058] Weigh 10 parts of cooked talc, 5 parts of additive modifier, 4 parts of ball clay, 4 parts of modified dolomite, 2 parts of Longquan porcelain clay, 2 parts of zinc oxide, and 2 parts of tin oxide by weight, and then wet-mill them thoroughly to obtain celadon glaze water;
[0059] Step 2: 10 parts of potassium feldspar, 4 parts of quartz, 3 parts of kaolin and 3 parts of bentonite are mixed and wet-milled by weight at a ball milling speed of 1000 r / min for 1 hour to obtain a ball mill; the ball mill is pressed into a mold at a pressing pressure of 15 MPa for 30 minutes to obtain a green body;
[0060] Step three: Apply celadon glaze to the surface of the body, and then sinter it. After sintering, a ceramic with celadon glaze is obtained.
[0061] The glaze amount of this embodiment is 520g / m 2 ; The sintering temperature of the sintering treatment is 1350°C and the sintering time is 5h.
[0062] The preparation method of adding a modifier in this embodiment is:
[0063] S01: Add 2 parts of zirconium silicate and 1 part of silane coupling agent KH550 to 5 parts of cerium nitrate solution by weight, then add 2 parts of silicon carbide powder and stir thoroughly to obtain zirconium silicate liquid;
[0064] S02: immersing the boron nitride in a 5% chitosan solution with a mass fraction of 3 times the total weight of the boron nitride, stirring evenly to obtain a boron nitride solution;
[0065] Adding boron nitride liquid to zirconium silicate liquid in a weight ratio of 2:5 and stirring, and completing the stirring to obtain a zirconium silicate agent doped with boron nitride;
[0066] S03: Add an additive of 10% of the total weight of the boron nitride-doped zirconium silicate to the boron nitride-doped zirconium silicate, and ball-mill at a speed of 750 r / min for 2 h. After the ball-milling is completed, filter and dry to obtain an additive modifier.
[0067] The mass fraction of the cerium nitrate solution in this embodiment is 2%; the stirring speed of the stirring process is 550 r / min, and the stirring time is 1 hour.
[0068] The preparation method of the additive of this embodiment is:
[0069] According to weight, 2 parts of yttrium oxide and 1 part of silica powder are added to 4 parts of sodium silicate solution, and then 2 parts of nano-attapulgite and 1 part of nano-silica sol are added, and the mixture is stirred and mixed thoroughly, and then filtered and dried to obtain an additive.
[0070] The mass fraction of the sodium silicate solution in this embodiment is 2%.
[0071] The modification method of the modified dolomite of the present embodiment is:
[0072] S101: placing the dolomite in a proton irradiation box and irradiating it for 10 minutes at an irradiation power of 350 W, and then preheating it at 60° C. for 1 hour after the irradiation to obtain pretreated dolomite;
[0073] S102: Mix 1 part of urea solution and 2 parts of dopamine hydrochloride solution by weight, then add 2 parts of hydroxyapatite and 1 part of sodium carboxymethyl cellulose, stir well, and obtain a modified solution;
[0074] The pretreated dolomite and the modified liquid were subjected to ultrasonic modification treatment in a weight ratio of 2:5. After the modification was completed, the modified dolomite was filtered and dried to obtain the modified dolomite.
[0075] The mass fraction of the urea solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 4%; the ultrasonic power of the ultrasonic modification treatment is 400 W, and the ultrasonic time is 1 hour.
[0076] A ceramic of this embodiment is prepared by the ceramic preparation method.
[0077] Embodiment 2: A method for preparing ceramics, comprising the following steps:
[0078] Step 1: Prepare celadon glaze:
[0079] Weigh 15 parts of cooked talc, 8 parts of additive modifier, 7 parts of ball clay, 7 parts of modified dolomite, 4 parts of Longquan porcelain clay, 4 parts of zinc oxide, and 4 parts of tin oxide by weight, and then wet-mill them thoroughly to obtain celadon glaze water;
[0080] Step 2: 15 parts of potassium feldspar, 7 parts of quartz, 5 parts of kaolin and 5 parts of bentonite are mixed and wet-milled by weight at a ball milling speed of 1000 r / min for 1 hour to obtain a ball mill; the ball mill is pressed into a mold at a pressing pressure of 15 MPa for 30 minutes to obtain a green body;
[0081] Step three: Apply celadon glaze to the surface of the body, and then sinter it. After sintering, a ceramic with celadon glaze is obtained.
[0082] The glaze amount of this embodiment is 550g / m 2 ; The sintering temperature of the sintering treatment is 1350°C and the sintering time is 5h.
[0083] The preparation method of adding a modifier in this embodiment is:
[0084] S01: Add 5 parts of zirconium silicate and 3 parts of silane coupling agent KH550 to 5-8 parts of cerium nitrate solution by weight, then add 3 parts of silicon carbide powder and stir well to obtain zirconium silicate liquid;
[0085] S02: immersing the boron nitride in a 5% chitosan solution with a mass fraction of 5 times the total weight of the boron nitride, stirring evenly to obtain a boron nitride solution;
[0086] Adding boron nitride liquid to zirconium silicate liquid in a weight ratio of 2:5 and stirring, and completing the stirring to obtain a zirconium silicate agent doped with boron nitride;
[0087] S03: Add an additive of 15% of the total weight of the boron nitride-doped zirconium silicate agent to the boron nitride-doped zirconium silicate agent, and ball-mill at a speed of 850 r / min for 2 hours. After the ball-milling is completed, filter and dry to obtain an additive modifier.
[0088] The mass fraction of the cerium nitrate solution in this embodiment is 5%; the stirring speed of the stirring process is 750 r / min, and the stirring time is 1 hour.
[0089] The preparation method of the additive of this embodiment is:
[0090] According to weight, 4 parts of yttrium oxide and 3 parts of silica powder are added to 7 parts of sodium silicate solution, and then 4 parts of nano-attapulgite and 2 parts of nano-silica sol are added, and the mixture is stirred and mixed thoroughly, and then filtered and dried to obtain an additive.
[0091] The mass fraction of the sodium silicate solution in this embodiment is 5%.
[0092] The modification method of the modified dolomite of the present embodiment is:
[0093] S101: placing the dolomite in a proton irradiation box and irradiating it for 15 minutes at an irradiation power of 400 W, and then preheating it at 65° C. for 1 hour after the irradiation is completed to obtain pretreated dolomite;
[0094] S102: Mix 2 parts of urea solution and 4 parts of dopamine hydrochloride solution by weight, then add 3 parts of hydroxyapatite and 2 parts of sodium carboxymethyl cellulose, stir well, and obtain a modified solution;
[0095] The pretreated dolomite and the modified liquid were subjected to ultrasonic modification treatment in a weight ratio of 2:5. After the modification was completed, the modified dolomite was filtered and dried to obtain the modified dolomite.
[0096] The mass fraction of the urea solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 6%; the ultrasonic power of the ultrasonic modification treatment is 450W, and the ultrasonic time is 1h.
[0097] A ceramic of this embodiment is prepared by the ceramic preparation method.
[0098] Embodiment 3: A method for preparing ceramics, comprising the following steps:
[0099] Step 1: Prepare celadon glaze:
[0100] Weigh 12.5 parts of cooked talc, 6.5 parts of additive modifier, 5.5 parts of ball clay, 5.5 parts of modified dolomite, 3 parts of Longquan porcelain clay, 3 parts of zinc oxide, and 3 parts of tin oxide according to weight.
[0101] , and then wet ball milling to obtain celadon glaze water;
[0102] Step 2: 12.5 parts of potassium feldspar, 5.5 parts of quartz, 4 parts of kaolin and 4 parts of bentonite are mixed by wet ball milling at a ball milling speed of 1000 r / min for 1 hour to obtain a ball mill material; the ball mill material is pressed into a mold at a pressing pressure of 15 MPa for 30 minutes to obtain a green body;
[0103] Step three: Apply celadon glaze to the surface of the body, and then sinter it. After sintering, a ceramic with celadon glaze is obtained.
[0104] The glaze amount of this embodiment is 535g / m 2 ; The sintering temperature of the sintering treatment is 1350°C and the sintering time is 5h.
[0105] The preparation method of adding a modifier in this embodiment is:
[0106] S01: Add 3.5 parts of zirconium silicate and 2 parts of silane coupling agent KH550 to 6.5 parts of cerium nitrate solution by weight, then add 2.5 parts of silicon carbide powder, stir well, and obtain zirconium silicate liquid;
[0107] S02: immersing the boron nitride in a 5% chitosan solution having a mass fraction of 4 times the total weight of the boron nitride, stirring evenly to obtain a boron nitride solution;
[0108] Adding boron nitride liquid to zirconium silicate liquid in a weight ratio of 2:5 and stirring, and completing the stirring to obtain a zirconium silicate agent doped with boron nitride;
[0109] S03: Add 12.5% of the total weight of the boron nitride-doped zirconium silicate agent to the boron nitride-doped zirconium silicate agent, and ball-mill at a speed of 800 r / min for 2 h. After the ball-milling is completed, filter and dry to obtain an additive modifier.
[0110] The mass fraction of the cerium nitrate solution in this embodiment is 3.5%; the stirring speed of the stirring treatment is 600 r / min, and the stirring time is 1 hour.
[0111] The preparation method of the additive of this embodiment is:
[0112] According to weight, 3 parts of yttrium oxide and 2 parts of silica powder are added to 5.5 parts of sodium silicate solution, and then 3 parts of nano-attapulgite and 1.5 parts of nano-silica sol are added, and the mixture is stirred and mixed thoroughly, and then filtered and dried to obtain an additive.
[0113] The mass fraction of the sodium silicate solution in this embodiment is 3.5%.
[0114] The modification method of the modified dolomite of the present embodiment is:
[0115] S101: placing the dolomite in a proton irradiation box and irradiating it for 12.5 minutes at an irradiation power of 375 W, and then preheating it at 62.5° C. for 1 hour after the irradiation is completed to obtain pretreated dolomite;
[0116] S102: Mix 1.5 parts of urea solution and 3 parts of dopamine hydrochloride solution by weight, then add 2.5 parts of hydroxyapatite and 1.5 parts of sodium carboxymethyl cellulose, stir well, and obtain a modified solution;
[0117] The pretreated dolomite and the modified liquid were subjected to ultrasonic modification treatment in a weight ratio of 2:5. After the modification was completed, the modified dolomite was filtered and dried to obtain the modified dolomite.
[0118] The mass fraction of the urea solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 5%; the ultrasonic power of the ultrasonic modification treatment is 425W, and the ultrasonic time is 1h.
[0119] A ceramic of this embodiment is prepared by the ceramic preparation method.
[0120] Comparative Example 1:
[0121] The difference from Example 3 is that no modifier is added to the preparation of the celadon glaze water.
[0122] Comparative Example 2:
[0123] The difference from Example 3 is that the boron nitride-doped zirconium silicate agent is not added in the preparation of the added modifier.
[0124] Comparative Example 3:
[0125] The difference from Example 3 is that no boron nitride liquid is added in the preparation of the boron nitride-doped zirconium silicate agent.
[0126] Comparative Example 4:
[0127] The difference from Example 3 is that no zirconium silicate liquid is added in the preparation of the boron nitride-doped zirconium silicate agent.
[0128] Comparative Example 5:
[0129] Different from Example 3, zirconium silicate and silane coupling agent KH550 were not added to the zirconium silicate liquid.
[0130] Comparative Example 6:
[0131] The difference from Example 3 is that silicon carbide powder is not added to the zirconium silicate solution, and water is used instead of the cerium nitrate solution.
[0132] Comparative Example 7:
[0133] The difference from Example 3 is that no additives were added during the preparation of the modified agent.
[0134] Comparative Example 8:
[0135] The difference from Example 3 is that no modified dolomite is added to the preparation of the celadon glaze water.
[0136] Comparative Example 9:
[0137] The difference from Example 3 is that no pretreated dolomite is added in the preparation of the modified dolomite. The specific preparation method is as follows:
[0138] According to weight, mix 1.5 parts of urea solution and 3 parts of dopamine hydrochloride solution, then add 2.5 parts of hydroxyapatite and 1.5 parts of sodium carboxymethyl cellulose, stir thoroughly, filter and dry.
[0139] Comparative Example 10:
[0140] The difference from Example 3 is that no modifying liquid is added for ultrasonic modification treatment during the preparation of the modified dolomite.
[0141] Comparative Example 11:
[0142] The difference from Example 3 is that hydroxyapatite and sodium carboxymethyl cellulose are not added to the modified solution.
[0143] Comparative Example 12:
[0144] The difference from Example 3 is that no urea solution is added to the modified liquid and the dopamine hydrochloride solution is replaced by water.
[0145] The ceramic products of Examples 1-3 and Comparative Examples 1-12 were tested under normal conditions for surface wear resistance (wear test in a testing machine with a load of 5N and a rotation speed of 50r / min), impact strength and texture fineness. The test results are shown in Table 1.
[0146] Table 1 Performance test results of the products of Examples 1-3 and Comparative Examples 1-12 under normal conditions:
[0147]
[0148] It can be concluded from Examples 1-3 and Comparative Examples 1-12 that the ceramic product of Example 3 of the present invention has significant performance effects in terms of wear resistance, impact strength and fine texture, and the performance of the ceramic product can be improved in a coordinated manner.
[0149] The ceramic products of Examples 1-3 and Comparative Examples 1-12 were placed in 3% hydrochloric acid mist for 12 hours, and then in 3% sodium hydroxide alkaline mist for 12 hours, and the acid and alkali stability under the condition of 3% mass fraction was tested. The products were placed in 8% hydrochloric acid mist for 12 hours, and then in 8% sodium hydroxide alkaline mist for 12 hours, and the acid and alkali stability under the condition of 8% mass fraction was tested. The test results are shown in Table 2.
[0150] Table 2 Performance test results of the products of Examples 1-3 and Comparative Examples 1-12 under acid and alkaline conditions:
[0151] From the comparative examples 1-12 and the example 3 and the acid and alkali resistance, it can be seen that the ceramic product of the example 3 has a significant effect on the stability of the performance of the ceramic product under the acid and alkali conditions of 3% and 8% respectively;
[0152] When neither the modified agent nor the modified dolomite is added to the celadon glaze water, the product performance deteriorates significantly. Only when the two are combined and work together, the product performance effect is most significant.
[0153] In the preparation of the added modifier, the boron nitride-doped zirconium silicate agent was not added, the boron nitride liquid was not added in the preparation of the boron nitride-doped zirconium silicate agent, the zirconium silicate liquid was not added in the preparation of the boron nitride-doped zirconium silicate agent, the zirconium silicate liquid was not added with zirconium silicate, the silane coupling agent KH550, the zirconium silicate liquid was not added with silicon carbide powder, the cerium nitrate solution was replaced by water, and the additives were not added in the preparation of the added modifier. The performance of the product showed a trend of deterioration to varying degrees, and the performance of the product deteriorated significantly when the additives were not added in the preparation of the added modifier;
[0154] At the same time, the boron nitride-doped zirconium silicate agent obtained by combining the zirconium silicate liquid obtained by the specific method of the present invention with the boron nitride liquid, and the additive modifier prepared by combining the additives, the performance effect of the product is the most significant, and the effect of using other methods instead is not as obvious as that of the present invention;
[0155] At the same time, in the preparation of the modified dolomite, no pretreated dolomite was added, no modifying liquid was added for ultrasonic modification, no hydroxyapatite and sodium carboxymethyl cellulose were added to the modifying liquid, no urea solution was added to the modifying liquid, and water was used instead of the dopamine hydrochloride solution. The performance of the product also showed a trend of deterioration to varying degrees. The performance effect of the product was the most significant when the modifying liquid obtained by the specific method of the present invention was combined with the pretreated dolomite.
[0156] Based on the above tests, the present invention further explores the product performance by adding materials.
[0157] Experimental Example 1:
[0158] The same as Example 3, the only difference is that no silica powder is added to the additive.
[0159] Experimental Example 2:
[0160] The same as Example 3, the only difference is that yttrium oxide is not added to the additive.
[0161] Experimental Example 3:
[0162] The same as Example 3, the only difference is that no nano-attapulgite is added to the additive.
[0163] Experimental Example 4:
[0164] The same as Example 3, the only difference is that no nano silica sol is added to the additive.
[0165] Experimental Example 5:
[0166] The same as Example 3, the only difference is that the sodium silicate solution in the additive is replaced by water.
[0167] The ceramic products of Experimental Examples 1-5 were placed in 3% hydrochloric acid mist for 12 hours, and then placed in 3% sodium hydroxide alkaline mist for 12 hours, and the acid and alkali stability under the mass fraction of 3% was tested. The products were placed in 8% hydrochloric acid mist for 12 hours, and then placed in 8% sodium hydroxide alkaline mist for 12 hours, and the acid and alkali stability under the mass fraction of 8% was tested. The test results are shown in Table 3.
[0168] Table 3 Performance test results of the products of Experimental Examples 1-5 under acid and alkaline conditions:
[0169] It can be seen from Experimental Examples 1-5 that when no nano-attapulgite and no silica powder were added to the additives, the performance of the ceramic products showed a more obvious trend of deterioration. At the same time, when no yttrium oxide and nano-silica sol were added to the additives, and the sodium silicate solution was replaced by water, the performance of the ceramic products showed a trend of deterioration. The additives obtained by the specific method of the present invention have the most obvious performance effect on the ceramic products, and the effects of other methods are not as significant as those of the present invention.
[0170] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0171] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A celadon glaze, characterized in that: It includes the following raw materials in parts by weight: 10-15 parts of cooked talc, 5-8 parts of additive modifier, 4-7 parts of ball clay, 4-7 parts of modified dolomite, 2-4 parts of Longquan porcelain clay, 2-4 parts of zinc oxide, 2-4 parts of tin oxide; The preparation method of adding a modifier is: S01: Add 2-5 parts of zirconium silicate and 1-3 parts of silane coupling agent KH550 to 5-8 parts of cerium nitrate solution by weight, then add 2-3 parts of silicon carbide powder, stir well, and obtain zirconium silicate liquid; S02: immersing the boron nitride in a 5% chitosan solution having a mass fraction of 3-5 times the total weight of the boron nitride, stirring evenly to obtain a boron nitride solution; Adding boron nitride liquid to zirconium silicate liquid and stirring, the weight ratio of boron nitride liquid to zirconium silicate liquid is 2:5, and stirring is completed to obtain a boron nitride-doped zirconium silicate agent; S03: adding an additive of 10-15% of the total weight of the boron nitride-doped zirconium silicate agent to the boron nitride-doped zirconium silicate agent, ball milling at a speed of 750-850 r / min for 2 hours, filtering and drying after the ball milling is completed to obtain an additive modifier; The preparation method of the additive is: According to weight, 2-4 parts of yttrium oxide and 1-3 parts of silica powder are added to 4-7 parts of sodium silicate solution, and then 2-4 parts of nano-attapulgite and 1-2 parts of nano-silica sol are added, and the mixture is stirred and mixed thoroughly, and then filtered and dried to obtain an additive; The modification method of the modified dolomite is: S101: placing the dolomite in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400W. After the irradiation is completed, preheating at 60-65° C. for 1 hour to obtain pretreated dolomite; S102: Mix 1-2 parts of urea solution and 2-4 parts of dopamine hydrochloride solution by weight, then add 2-3 parts of hydroxyapatite and 1-2 parts of sodium carboxymethyl cellulose, stir well, and obtain a modified solution; The pretreated dolomite and the modified liquid were subjected to ultrasonic modification treatment in a weight ratio of 2:
5. After the modification was completed, the modified dolomite was filtered and dried to obtain the modified dolomite.
2. The celadon glaze according to claim 1, characterized in that: The mass fraction of the cerium nitrate solution is 2-5%; the stirring speed of the stirring treatment is 550-750 r / min, and the stirring time is 1 hour.
3. The celadon glaze according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%.
4. The celadon glaze according to claim 1, characterized in that: The mass fraction of the urea solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 4-6%; the ultrasonic power of the ultrasonic modification treatment is 400-450W, and the ultrasonic time is 1h.
5. A method for preparing ceramics, using the celadon glaze water as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Prepare celadon glaze: Weigh the raw materials of celadon glaze water by weight, and then wet-mill them thoroughly to obtain celadon glaze water; Step 2: 10-15 parts of potassium feldspar, 4-7 parts of quartz, 3-5 parts of kaolin and 3-5 parts of bentonite are mixed and wet-milled at a speed of 1000 r / min for 1 hour to obtain a ball mill; the ball mill is pressed into a mold at a pressure of 15 MPa for 30 minutes to obtain a green body; Step three: Apply celadon glaze to the surface of the body, and then sinter it. After sintering, a ceramic with celadon glaze is obtained.
6. The method for preparing ceramics according to claim 5, characterized in that: The glazing amount of the glazing is 520-550g / m 2 ; The sintering temperature of the sintering treatment is 1350°C and the sintering time is 5h.
7. A ceramic prepared by the method for preparing a ceramic according to claim 5 or 6.
Citation Information
Patent Citations
Environment-friendly self-cleaning negative-ion ceramic brick and making method of ceramic brick
CN109095910A